The impact of TikTok addiction on depression, anxiety and stress severity among university students - Mohd Nor Shokri, Nur Shafira Izzatie; Elsayed, Tarek Mohamed Ali; Fata Nahas, Abdul Rahman (IIUM Press, 2025)
Background: TikTok’s personalized content and short video format have contributed to its widespread popularity, particularly among university students. However, these same features make it potentially addictive, raising concerns about its impact on mental health. This study aims to examine the relationship between TikTok addiction and levels of depression, anxiety, and stress among university students in Malaysia.